Multisectoral Action to Combat Regional and Social Inequities in Health 2017
DOI: 10.26911/theicph.2017.093
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing Female Infertility

Abstract: Background: Female infertility is one of important public health problems worldwide. According to the World Health Organization, the incidence of infertile cases is increasing each year. Likewise, according to the Central Bureau of Statistics, infertile incidence in Indonesia has been increasing. Dr. Moewardi Hospital Surakarta is one of the hospitals in Central Java Province with increasing number of infertile patients visits. This study aimed to analyze risk factors influencing female infertility. Subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Research by Ika Indarwati et al The results of the study concluded that female infertility is affected by age ≥35 years, risky work, high stress levels, abnormal body mass index, and abnormalities of the reproductive organs. (Indarwati et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Ika Indarwati et al The results of the study concluded that female infertility is affected by age ≥35 years, risky work, high stress levels, abnormal body mass index, and abnormalities of the reproductive organs. (Indarwati et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Membentuk keluarga yang bahagia berkaitan erat dengan masalah keturunan (Hidayah & Hadjam, 2007). Kehadiran seorang anak merupakan suatu dambaan bagi setiap pasangan suami istri apalagi bagi mereka yang telah lama menikah (Indarwati, Hastuti, & Dewi, 2017). Keluarga memandang anak yang baru lahir sebagai simbol menjaga keturunan mereka untuk tetap bertahan dan seseorang tersebut yang akan menjadi penerus nama keluarga dan tradisi ke generasi berikutnya (Saleem, Qureshi, & Mahmood, 2019).…”
Section: Pendahuluanunclassified
“…However, the unmet need for spacing still has to be handled because of the fertile period a woman is limited to a certain age so that it affects birth control. The increasing age of a woman will results in hormonal imbalances in the body and decreased function of reproductive organs, resulting in a decrease in female fertility [5]. Research in India shows a significant effect of the contraceptive needs fulfillment for thinning by birth control [6].…”
Section: Introductionmentioning
confidence: 99%